The export behaviour of Spanish manufacturers: An evaluation of interviews - Juan Viúdez (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1972)
Spanish industrial exports have shown considerable change over the last decade in both level and composition. It seems appropriate to conduct research at the firm level in order to gain some knowledge concerning the soundness and "staying power" of the recent export upsurge. 65 firms were interviewed for this purpose. Export prospects until 1975 vary considerably among firms. Many firms are not able to give an estimate about future export activities - which, reportedly, can be attributed to the fact that planning is one of the weakest areas of management in Spain. Manufactured exports are likely to become more important in the future since entrepreneurs are becoming aware of the increasing saturation on the home market. Therefore, they may react by seeking export outlets for their production. Traditional export industries, using labour-intensive and/or raw material-intensive processes, are able to sell abroad at the same price as in the domestic market. For some non-traditional export industries producing technologically standardized goods there is no price differential either. Other new exporting industries still have to price their sales abroad considerably below the domestic prices. No conclusive relationship was found between estimated export performance and firm size. Interestingly enough, the small firms in the sample do not consider size as such to pose a serious disadvantage in exporting. There is evidence about the negative influence on exports of clauses in the licensing agreements with foreign investors forbidding or restricting foreign sales. The stand of the Spanish Government against such restrictive business practices is often easily sidestepped through informal "gentlemen's agreements." For many exporters the main problem in selling abroad is the fact that they are not yet known and that Spanish products have to overcome the resistance arising from a poor industrial image. This situation may improve as foreign investors make available marketing facilities to the Spanish industry.
Keywords: 330